Injectable Platelet-Rich Fibrin and Advanced Platelet-Rich Fibrin Demonstrate Enhanced Anti-Biofilm Effect Compared to Enamel Matrix Derivatives on Decontaminated Titanium Surfaces - Jothi Varghese; Liza L. Ramenzoni; Padmaja A. Shenoy; Patrick R. Schmidlin; Shubhankar Mehrotra; Vinayak Kamath (MDPI AG, 2024)
Background: The search for effective antimicrobial agents to mitigate peri-implant infections remains a crucial aspect of implant dentistry. This study aimed to evaluate and compare the antimicrobial efficacy of i-PRF, A-PRF+, and enamel matrix derivative (EMD) on decontaminated rough and smooth titanium (Ti) discs. Materials and Methods: Rough and smooth Ti discs were coated with multispecies biofilm and thoroughly debrided using a chitosan-bristled brush. Subsequently, i-PRF, A-PRF+, and EMD were applied. Untreated discs served as control. Residual adherent bacteria present on the treated Ti discs were visualized by SEM and quantified using culture technique, and colony-forming units (CFUs) were measured after 48 h and 7 days. Results: i-PRF demonstrated better antimicrobial effectiveness on both smooth and rough implant surfaces as compared to A-PRF+ and EMD (p < 0.001). In all the experimental groups, smooth Ti discs displayed a greater reduction in microbes compared to rough Ti discs when treated with the biologics. The major reduction in CFU values was determined after seven days. Conclusions: i-PRF as a regenerative material may also be suitable for decontaminating implant surfaces, which could influence tissue healing and regenerative outcomes positively.